THE SANCTION FORMULATION IN CORRUPTION CRIME DUE TO INDONESIAN CRIMINAL LAW SYSTEM TO REALIZE THE PUNISHMENT GOALS - Sudarti, Elly; L, Sahuri (Ganesha Law Review, 2019)
The Formulation of Criminal Sanctions holds a strategic position in an effort to decrease corruption crime. Until now, the application of criminal sanctions in Indonesia has not provided a direction for the occurrence of a significant decrease in corruption. This can be seen from the issued by Transparency International 2017 about the ranking of the most corrupt countries in the world, where Indonesia still in the 5thranks in ASEAN. This research purposes to analyze and to formulate the harmony in the formulation of criminal sanctions for corruption, with the goal of Indonesian criminalizing law system so that the ultimate goal is suppressing the level of corruption in Indonesia can be achieved. This study is used the statute, conceptual and case approach as a method to analyze the legal substances and the results of this research had been shown, there are several weaknesses in the criminal punishment system according to The Act Number 31 on 1999 andThe Act Number 20 on 2001; where, the system of corruption criminalizing is complicated that make the punishment for corruption cannot reach the goal of punishment. For the better law system in the future, it is more appropriate criminal sanctions needed to be formulated, so that the purpose of criminal penalties for corruption can be achieved, used by conducting a plea bargaining in the beginning, that the perpetrator must return state losses and pay fines but still be found guilty through the determination of the judge.